Adherence to antihypertensive medications for secondary prevention of cardiovascular disease events: a dose-response meta-analysis. (July 2021) - Feng, Y.; Han, M.; Qie, R.; Huang, S.; Li, Q.; Guo, C.; Tian, G.; Zhao, Y.; Yang, X.; Li, Y.; Wu, X.; Zhou, Q.; et al.
Abstract: Objectives: The aim of the study was to explore the association between adherence to antihypertensive medications (AHMs) and the risk of recurrence of cardiovascular disease (CVD) events in patients with a history of CVD events from cohort studies. Study design: This is a dose-response meta-analysis. Methods: PubMed and Embase databases were searched up to March 4, 2021, to identify English-language reports of cohort studies that assessed the association of AHM adherence with risk of recurrence of CVD events. Pooled relative risks (RRs) and 95% confidence intervals (CIs) were estimated by using a fixed- or random-effects model. Restricted cubic splines were used to evaluate the possible linear or non-linear association. Results: We included nine cohort studies (54, 349 patients) in the present meta-analysis. The pooled RR of CVD events was 0.66 (95% CI, 0.54–0.78) for the highest versus lowest AHM adherence category. We did not find any evidence of non-linearity association between AHM adherence and risk of CVD events ( P non-linearity  = 0.534); for patients with a history of CVD events, the risk of CVD events was reduced by 9% for each 20% increase in AHM adherence (RR, 0.91; 95% CI, 0.85–0.97). The results of sensitivity analysis and subgroup analysis were virtually unchanged. Conclusions: The high level of adherence to AHM is an effective strategy for preventing recurrence of CVD events. Patients with a history of CVD events should adhere to AHM.